Robin Phillips' Strange and Wondrous Dream - Knowles, Richard Paul (Theatre Research in Canada / Recherches théâtrales au Canada, 1988)
Robin Phillips' 1976-77 production of A Midsummer Night's Dream at the Stratford Festival has been one of the few since Peter Brook's 1970 production to carve out its own vision of the play. By mounting the production as a dream vision in the mind of Elizabeth I, Phillips discovered an extraordinary unity among the worlds of court and forest, and found analogies with the court of Elizabeth that brought out often neglected aspects of the play in a highly theatrical way. La mise en scène par Robin Phillips du Songe d'une nuit d'été à Stratford en 1976-1977 représente l'une des rares réalisations, depuis celle de Peter Brook en 1970, qui ait offert une vision originale de cette pièce de Shakespeare. En montant la pièce sous forme d'une vision apparue à Elisabeth Ière, Phillips aurait découvert des parallèles frappants entre la cour et la forêt, et retrouvé des liens avec la Cour d'Elisabeth qui soulignent, de façon fort théâtrale, certains aspects de l'oeuvre jusque-là souvent négligés.